Long‐term storage effects in steroid metabolite extracts from baboon (Papio sp.) faeces – a comparison of three commonly applied storage methods. Issue 5 (26th April 2013) - Kalbitzer, Urs; Heistermann, Michael; Rands, Sean
Summary The measurement of steroid hormone metabolites from faeces in wild animal populations is a powerful, noninvasive tool in behavioural endocrinology of all major vertebrate taxa. However, because such research is often done in remote areas with limited infrastructure, storage of samples for hormone analysis over long periods at high temperature is a critical issue in field endocrinology. Previous studies have indicated that storage of alcoholic faecal extracts is more reliable than storage of unprocessed faeces if no freezer is available, but a standard method has not been established yet. We tested the validity of three commonly applied storage conditions – liquid extracts, dried extracts and extracts placed on solid‐phase extraction (SPE) cartridges – to preserve concentrations of glucocorticoid and androgen metabolites from faecal extracts of olive baboons (Papio anubis) at high temperature over 1 year. Temporal variation in concentrations was detected for all metabolites and all storage conditions, including values measured from the control condition, that is, extracts stored at −20°C. This suggested that most variation was due to interassay variability, corroborated by comparisons of variation in 'quality controls' and samples. Compared to frozen control samples, liquid extracts were stable for up to 24 weeks, extracts on SPE cartridges were stable for up to 50 weeks, while steroid metabolite concentrations in dried extracts decreased slightly over time. If steroid samples have to be stored at ambient temperature, we suggest storage of liquid extracts for up to 24 weeks in a dark and cool place. For longer periods, SPE cartridges should be applied as evaporation, a potential confound arising with long‐term storage of liquid extracts at higher temperatures, is not a problem in this storage condition. Storage of dried extracts is more cost‐effective, but may result in small time‐dependent changes in steroid concentrations.